Effects of biochar on the fate of the heavy metals Cd, Cu, Pb and Zn in soil - Khan, KT; Chowdhury, MTA; Huq, SM Imamul (Bangladesh Journal of Scientific Research, 2016)
An in vitro incubation study was conducted with soil having seven applications of different treatments of biomass and biochar including a control. The biochar and biomasses were applied at a rate of 5 t ha-1 and incubated at field moisture condition for 30, 60 and 90 days individually in different pots. 0.005M DTPA and 1M HCl extractable cadmium (Cd), copper (Cu), lead (Pb) and zinc (Zn) contents were determined at 30, 60 and 90 days of incubation. The phytoavailable fraction of Cd, Cu, Pb and Zn as extracted with the 0.005M DTPA revealed that biochar did not retain any substantial amount of any of these metals. 1M HCl extracted higher amounts of heavy metals than 0.005M DTPA. Neither biochar nor its source biomass had any sorptive effect on the labile fraction of Pb and Cd present in soil. 1M HCl extracted not only a portion of these metals from the soils but also that present in the biochar and biomass. The general idea that biochars are able to complex metal ions on their surfaces and therefore, reduce bioavailability, however, was not reflected in the present study. Bangladesh J. Sci. Res. 28(1): 17-26, June-2015